Enhancing the Quality of Care in Long-Term Care Settings - Devi, Reena; Dening, Tom; Gordon, Adam (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Quality of care in long-term care is a worldwide issue given the growing numbers of dependent older people. This book presents international research, 22 varied papers, exploring quality of care from several different angles. Important themes include: (1) workforce issues, such as staff training and support; job competencies, satisfaction, and intention to stay in work; staff burnout; effects of personal- and work-related factors on quality of care; (2) intervention studies: for depressive symptoms in nursing home residents; adjustment for new residents; social and psychological support; and loneliness and isolation; (3) methodology, including: developing and testing quality indicators; measuring residents' experience of quality; and assessing partnership between staff and families; and (4) older people's experiences, such as dry eyes and using ocular lubricants; associations between length of stay and end of life care; palliative care service use and comfort at end of of life; and causes of infection-related hospitalization. The book concludes with a systematic review of the current evidence base of care home research in Brazil.